Polymerization mechanism, micro-macro properties, and carbonization of polyurethane foams - Xu, Jie (2017)
Polyurethane is one of the most diversified macropolymers with versatile properties for many applications including construction, transportation, personal wear, household appliance, etc. The research of this PhD study covers many aspects of polyurethane, including modelling on urethanisation and foaming mechanism, cell microstructure and packing polyhedrons, macroscopic properties and performance, and functional carbon materials developed from carbonisation of polyisocyanurate (PIR) foams. The work contains both theoretical modelling and experimental measurements.